2021
DOI: 10.1097/acm.0000000000004399
|View full text |Cite
|
Sign up to set email alerts
|

A Distance-Learning Approach to Point-of-Care Ultrasound Training (ADAPT): A Multi-Institutional Educational Response During the COVID-19 Pandemic

Abstract: ProblemThe COVID-19 pandemic significantly disrupted point-of-care ultrasound (POCUS) education. Medical schools and residency programs placed restrictions on bedside teaching and clinical scanning as part of risk mitigation. In response, POCUS faculty from 15 institutions nationwide collaborated on an alternative model of ultrasound education, A Distance-learning Approach to POCUS Training (ADAPT). ApproachADAPT was repeated monthly from April 1 through June 30, 2020. It accommodated 70 learners, who included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Some of these approaches proved to be imperative for adapting US curricula for distance learning due to the Covid‐19 pandemic, as additional resources were required to provide hands‐on training to learners in different locations. While the pandemic forced most US curricula to be canceled, those that were adapted for virtual learning required extra faculty for lower in‐person faculty to student ratios and handheld US devices (Nix et al, 2021), additional tele‐US software and training (Soni et al, 2021), or didactic and US interpretation modules with lack of supervised hands‐on training (Boulger et al, 2021). Despite the additional resources, each of these studies found success in translating their US curricula, reinforcing the ability share approaches across institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these approaches proved to be imperative for adapting US curricula for distance learning due to the Covid‐19 pandemic, as additional resources were required to provide hands‐on training to learners in different locations. While the pandemic forced most US curricula to be canceled, those that were adapted for virtual learning required extra faculty for lower in‐person faculty to student ratios and handheld US devices (Nix et al, 2021), additional tele‐US software and training (Soni et al, 2021), or didactic and US interpretation modules with lack of supervised hands‐on training (Boulger et al, 2021). Despite the additional resources, each of these studies found success in translating their US curricula, reinforcing the ability share approaches across institutions.…”
Section: Discussionmentioning
confidence: 99%
“… 274 The response of educational institutions to pandemic‐related restrictions in US education has boosted the application of virtual educational formats including real‐time supervised practical training. 275 , 276 , 277 , 278 …”
Section: Methodsmentioning
confidence: 99%
“…274 The response of educational institutions to pandemicrelated restrictions in US education has boosted the application of virtual educational formats including real-time supervised practical training. [275][276][277][278] Scientific societies related to LUS have already issued minimum requirements. 279 For education and training purposes, LUS can further be broken down into modalities with basic to advanced level qualification.…”
Section: Guidelinesmentioning
confidence: 99%
“…A number of studies describe successful collaboration across two sites using telementoring, in some cases between vast distances. [31][32][33][34] They demonstrate the tangible value of this technology to patients and trainees where expert ultrasound guidance may not be readily available because of the remote nature of the location. Telementoring offers the opportunity to provide ultrasound training in areas that would otherwise not have the expertise to guide trainees and optimise the management of patients.…”
Section: Telementoringmentioning
confidence: 98%